Exploring the Influence of Big Five Personality Traits on Entrepreneurial Intention among University Students - Pang, Chia Xuan; Chan, Shiau Wei; Ahmad, Ahmad Nur Aizat; Ahmad, Md Fauzi; Ismail, Fadillah; Zaman, Izzuddin (Research in Management of Technology and Business, 2025)
Entrepreneurship is critical for economic growth, innovation, and job creation, particularly in emerging economies like Malaysia. Despite high employability rates, many Universiti Tun Hussein Onn Malaysia (UTHM) graduates opt for traditional employment over entrepreneurial ventures. Thus, this study examines the levels of the Big Five personality traits and entrepreneurial intention (EI) among UTHM students, assesses the relationships between these traits and EI, and evaluates their effects on EI. A quantitative research design was employed, with data collected from 320 Faculty of Technology Management and Business (FPTP) students through an online survey. The survey utilized validated instruments measured on a five-point Likert scale, and the data were analyzed using SPSS version 27 through descriptive statistics, correlation, and regression analysis. The descriptive analysis revealed that UTHM students exhibit high levels of extraversion, agreeableness, conscientiousness, neuroticism, and openness to experience. The correlation analysis indicated significant positive relationships between extraversion, agreeableness, conscientiousness, and openness to experience with EI, while neuroticism showed a negative correlation with EI. Regression analysis further identified extraversion, neuroticism, and openness to experience as significant predictors of EI, with openness to experience being the strongest positive predictor. In contrast, agreeableness and conscientiousness did not have significant effects on EI. These results align with the research objectives and suggest that fostering traits such as openness to experience and extraversion through targeted educational strategies and policies could enhance students’ entrepreneurial intention, equipping them with skills to pursue entrepreneurial careers and contribute to Malaysia’s economic growth and innovation.